Sistem Pemilihan Lokasi Tower Bts (Base Tranciever Station) Menggunakan Metode Weighted Product (WP) - Saprudin Saprudin; Sholihin Sholihin; Nur Rofiq (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
Tower is a tower made of a series of iron or pipes with either a rectangular or triangular shape. In the early 1970s, scientist Michael S. Scott Morton introduced the concept of a decision support system with the term Management Decision System (Tampubolon, 2010). The purpose of this computer-based system is to assist decision making without eliminating the decision maker who utilizes existing data and models. The weighted product (WP) method was chosen in this open study because this method has the concept of improving weight in each of its criteria. This research will implement the weighted product (WP) method in the tower construction site selection system so that the location chosen for the construction of a BTS tower (Base Transcever Station) is more precise and in accordance with predetermined criteria, and so that the data reporting process and location information for development tower be fast.